Doping-induced transition from polycrystals to single crystals in ZnO thin films. (March 2020) - Xu, Linhua; Wang, Xiaoxiong; Xian, Fenglin; Su, Jing
Graphical abstract: When the Al-doping concentration is higher than 4at.%, the partial polycrystalline ZnO thin film will be transformed into single crystal ZnO nanostructures with a frustum of hexagonal pyramid shape. Highlights: High-quality ZnO thin films with a double-layer structure were obtained by Al doping. Doping-induced transition from polycrystals to single crystals in ZnO thin films was found. The effect of Al-doping concentration on the morphology evolution was investigated. The ZnO thin films with a double-layer structure showed a strong UV emission. Abstract: The growth of high quality ZnO thin films is a hot research topic in the field of optoelectronic materials. In this study, high quality ZnO thin films with a double-layer structure were obtained by sol-gel method. Al-doping induced transition from polycrystals to single crystals in the ZnO thin films was found. The results show that Al-doping improves the c-axis orientation of ZnO thin films. When the Al-doping concentration is higher than 4at%, the frustum of hexagonal pyramid (FHP) shaped ZnO nanostructures are formed on the polycrystalline ZnO thin films surface. As the Al-doping concentration further rises, the areal density of the FHP-shaped nanostructures also gradually increases and the size becomes more uniform. Both SAED patterns and high-resolution TEM images indicate that the FHP-shaped ZnO nanostructures are single crystals. It is of great scientific significance to transform polycrystalline ZnO into single crystal ZnO by Al-doping combined with a simple heat-treatment process. Compared with pure ZnO thin films, the FHP-shaped nanostructures on the surface show better UV emission performance, suggesting these materials are ideal ones for the preparation of ZnO-based UV emitters. The authors propose that the growth mechanism of FHP-shaped ZnO nanostructure is a multi-step solid-solid reaction dominated by surface diffusion of zinc atoms.